2021
DOI: 10.1002/csc2.20321
|View full text |Cite
|
Sign up to set email alerts
|

PLASTOCHRON1 regulates leaf inclination through Brassinolide pathway in Oryza sativa

Abstract: Leaf inclination directly affects the lamina angle of rice (Oryza sativa), which in turn affects the photosynthetic efficiency of the leaves and grain yield. A mutant s544 characterized by enhanced leaf inclination as well as small aerial organs was identified from the progeny of ethyl-methanesulfonate treated seeds of Indica rice 'Xida 1B'. Genetic analysis indicated that the mutant traits were controlled by a single recessive nuclear gene. Using a F 2 population derived from 'Jinhui 10' and the mutant, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Furthermore, it was shown that OsBUL1, LO9‐177 and OsBC1 form a tri‐protein complex that positively regulates LA in rice through regulating BR signalling and cell elongation in the lamina joint (Chen et al ., 2013; Jang et al ., 2017). Furthermore, it was reported that OsLC2 (encoding a VIN‐3 like protein), OsPLA1 (encoding a cytochrome P450 protein) and OsMDP1 (encoding a MADS DOMAIN‐CONTAINING PROTEIN) negatively regulate LA through controlling expansion and division of adaxial parenchyma cells of the lamina joint (Duan et al ., 2006; Xiong et al ., 2021; Zhao et al ., 2010). However, the detailed molecular mechanisms linking these genes to BR signalling remain to be elucidated in future studies.…”
Section: Regulation Of Ligule and Auricle Formationmentioning
confidence: 99%
“…Furthermore, it was shown that OsBUL1, LO9‐177 and OsBC1 form a tri‐protein complex that positively regulates LA in rice through regulating BR signalling and cell elongation in the lamina joint (Chen et al ., 2013; Jang et al ., 2017). Furthermore, it was reported that OsLC2 (encoding a VIN‐3 like protein), OsPLA1 (encoding a cytochrome P450 protein) and OsMDP1 (encoding a MADS DOMAIN‐CONTAINING PROTEIN) negatively regulate LA through controlling expansion and division of adaxial parenchyma cells of the lamina joint (Duan et al ., 2006; Xiong et al ., 2021; Zhao et al ., 2010). However, the detailed molecular mechanisms linking these genes to BR signalling remain to be elucidated in future studies.…”
Section: Regulation Of Ligule and Auricle Formationmentioning
confidence: 99%